Enhancing ERP Research through the Integration of Complementary Frameworks Brings New Insights and a Holistic Approach to Understanding Enterprise Resource Planning - Alam, Roslina; Tenrisau, Muhammad Aksan; Amirullah, Amirullah (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Since the early 1990s, the complexity of ERP systems has posed a challenge for practitioners, but the amount of empirical research exploring new ERP projects has increased over the past ten years. The progress of information technology (IT) has been disrupted by the emergence of new trending and rapidly evolving topics, causing the focus of information systems (IS) research to continuously shift to new issues before the theory or normative knowledge for existing topics is fully developed. The situation occurring in ERP research reflects a problem hindering the progress of the IS discipline: widespread dissatisfaction with the delay between the practical issues faced by practitioners and the normative knowledge generated by academic research. Using ERP as an example, this paper presents two main arguments: (a) IT-based innovations can be addressed by recognizing the important patterns behind each emerging IT phenomenon; and (b) once these important patterns are recognized, a complementary logic between variance- and process-oriented lessons can be proposed, which benefits the advancement of the ERP research model and provides relevant and timely practical lessons.